ENHANCING BUSINESS PERFORMANCE OF CV. BERKAT ANUGERAH MALANG USING ONLINE MARKETING STRATEGIES - Danny N. Gunawan; Ahmad Ihza Nailul F; Nicko Andrianto; Wendy Schoonderbeek (International Journal of Applied Business and International Management, 2017)
CV. Berkat Anugerah is the company focussed on Packaging and Bottling industry. After the identification of the factors concerning the internal and external factors on the company. the repair was undertaken as well as an increase in the company's strategy. the latest strategy is integrated with various concepts in business management. the latest strategy developed at the company's focus to enter international markets especially in the Asian region. Improving Exposure, Adding the Target Markets, and Use Personal Seller On Abroad. the strategy drawn up by various considerations such as a competitive advantage and the risks that may be encountered by the company.